Study of Strength and Deformation Evolution in Raw and Briquette Coal Samples under Uniaxial Compression via Monitoring Their Acoustic Emission Characteristics - Han Meng; Yuzhong Yang; Liyun Wu; Fei Wang; Lei Peng (Advances in Civil Engineering)
Briquette coals with different cement contents are frequently used to study the coal body’s properties. In this study, the deformation and strength of briquette coal samples with 0, 5, 10, and 20% cement contents were experimentally and theoretically investigated using the acoustic emission (AE) characteristics monitored during the uniaxial compression tests. The results show that the uniaxial compression process of raw coal and briquette coal samples can be subdivided into compaction, elastic, plastic (yield), and brittle failure stages. With an increase in cement content, briquette coal samples undergo the elastic and plastic stages, and their postpeak stress drop rate gradually grows, and their plastic deformation is followed by brittle failure. The uniaxial compressive strength and elastic modulus of briquette coal samples show a linearly increasing relationship with cement content, while their Poisson’s ratio decreases gradually. During the uniaxial compression, raw coal and briquette coal samples produce the AE signals. The overall AE signal of briquette coal samples is relatively low, and there are no obvious AE events in raw coal samples. The uniaxial compressive strength, elastic modulus, and Poisson’s ratio of briquette coal samples with a 20% cement content and their AE signal cumulative amplitude, count, and energy values are very close to the corresponding parameters of raw coal samples. Therefore, they can be used for simulating raw coal samples in laboratory tests.